Aerobic and anaerobic biological treatment of extracted chicken manure mixed with cassava dregs for potential use as liquid organic biofertilizer - Viagian Pastawan; Muhammad Daffa Shiddiq; Zulhammi Ahsan; Dimas Hand Vidya Paradhipta; Muhamad Khoiru Zaki; Mohammad Zainal Abidin; Nanung Agus Fitriyanto (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: This study aims to investigate the biological treatment of excreta wastewater to evaluate the effective production of liquid organic biofertilizer (LOB).Method: This research was carried out by the pre-initial mixing process of excreta with cassava dregs, then biological processing with the aeration rate of 4 L/minutes at environmental temperature (28 oC) and pH of 5 for 42 days with two treatments in triplicates: aerobically (T1), and anaerobically (T2) conditions. LOB was analyzed for physical, chemical, and microbiological parameters.Results: We showed that the characteristics of waste solids analysis of LOB were significantly decreased (P<0.05) in both aerobic and anaerobic treatment on the initial day of composting compared to the final day (42 days) by measuring the content of total solid (TS), total volatile solid (TVS), total fixed solid (TFS), and settleable solid (SS). Next, we showed the chemical properties of LOB respectively as follows: total N 6.73 mg/L and 7.31 mg/L; total P 36.27 mg/L and 87.17 mg/L; total K 640.85 mg/L and 674.82 mg/L; total C-organic 65.57 mg/L and 22.48 mg/L; and C/N ratio 10.13 and 3.5. The microbiological quality was evaluated at the end of LOB production by measuring total plate count (TPC) of 182000x105 cfu/ml and 203667x105 cfu/ml; total lactic acid bacteria of 31x105 cfu/ml and 32.67x105 cfu/ml; and there is no coliform growth observed in LOB, respectively.Conclusion: Finally, we concluded that the biological treatment is an important process in composting organic wastewater as a key to managing wastewater in the environment as reuse for liquid organic biofertilizer. The processing of excreta wastewater has managed to remove the total solid pollutants.